Fall risk assessment: it starts with you - Makhtar, Aniawanis (2023)
Fall risk assessment is a systematic evaluation process used to identify individuals who are at a higher risk of experiencing falls. Falls are a significant health concern, particularly among older adults, and can lead to injuries, reduced mobility, and a decline in overall well-being. Conducting a fall risk assessment helps healthcare professionals identify potential risk factors and implement preventive measures to reduce the likelihood of falls.